The Relationship Between Compulsive-Impulsive Behavior and Online Shopping Among Medical Students - Suandy Suandy; Nathasyia Aulia; Yolanda Eliza Putri Lubis (Jurnal Keperawatan Priority, 2025)
Compulsive and impulsive buying behaviors have become increasingly prevalent in modern society, particularly among medical students who have easy access to online shopping. This study aims to explore the relationship between compulsive and impulsive buying tendencies and online shopping behaviors among students from the Faculty of Medicine at Universitas Prima Indonesia, specifically the Class of 2023. Using an analytical survey method and a cross-sectional approach, data were collected from a purposive sample of 100 students. Questionnaires were administered to assess the levels of compulsive and impulsive buying. The results indicated a significant moderate positive correlation between compulsive and impulsive buying behaviors and online shopping, with a correlation coefficient of r=0.445 (p<0.001). This research aims to enhance the understanding of shopping behavior in the digital era and to assist in developing strategies to prevent unhealthy shopping habits.